Internal Versus External Motivation in Referral of Primary Care Patients with Depression to an Internet Support Group: Randomized Controlled Trial - Van Voorhees, Benjamin W; Hsiung, Robert C; Marko-Holguin, Monika; Houston, Thomas K; Fogel, Joshua; Lee, Royce; Ford, Daniel E (JMIR Publications, 2013)
BackgroundDepressive disorders and symptoms affect more than one-third of primary care patients, many of whom do not receive or do not complete treatment. Internet-based social support from peers could sustain depression treatment engagement and adherence. We do not know whether primary care patients will accept referral to such websites nor do we know which methods of referral would be most effective. ObjectiveWe conducted a randomized clinical trial to determine whether (1) a simple generic referral card (control), (2) a patient-oriented brochure that provided examples of online postings and experience (internal motivation), or (3) a physician letter of recommendation (external motivation) would generate the greatest participation in a primary care Internet depression treatment support portal focused around an Internet support group (ISG). MethodsWe used 3 offline methods to identify potential participants who had not used an ISG in the past 6 months. Eligibility was determined in part by a brief structured psychiatric interview based on the Patient Health Questionnaire-9 (PHQ-9). After consent and enrollment, participants were randomly assigned to 1 of 3 groups (control, internal motivation, or external motivation). We constructed a portal to connect primary care patients to both fact-based information and an established ISG (Psycho-Babble). The ISG allowed participants to view messages and then decide if they actually wished to register there. Participation in the portal and the ISG was assessed via automated activity tracking. ResultsFifty participants were assigned to the 3 groups: a motivation-neutral control group (n=18), an internal motivation group (n=19), and an external motivation group (n=13). Of these participants, 31 (62%) visited the portal; 27 (54%) visited the ISG itself. The internal motivation group showed significantly greater participation than the control group on several measures. The external motivation group spent significantly less time logged onto the portal than the control group. The internal motivation group showed significantly greater participation than the external motivation group on several measures. ConclusionsReferral of primary care patients with depressive disorders and symptoms to an ISG is feasible even if they have never previously used one. This may best be accomplished by enhancing their internal motivation. Trial RegistrationClinicaltrials.gov: NCT00886730; http://clinicaltrials.gov/show/NCT00886730 (Archived by WebCite at http://www.webcitation.org/6F4981fDN)